A Comprehensive Review and Update on the Pathogenesis of Inflammatory Bowel Disease - Qingdong Guan (Journal of Immunology Research)
Inflammatory bowel disease (IBD) is a chronic and life-threating inflammatory disease of gastroenteric tissue characterized by episodes of intestinal inflammation. The pathogenesis of IBD is complex. Recent studies have greatly improved our knowledge of the pathophysiology of IBD, leading to great advances in the treatment as well as diagnosis of IBD. In this review, we have systemically reviewed the pathogenesis of IBD and highlighted recent advances in host genetic factors, gut microbiota, and environmental factors and, especially, in abnormal innate and adaptive immune responses and their interactions, which may hold the keys to identify novel predictive or prognostic biomarkers and develop new therapies.